1993
DOI: 10.1016/0735-1097(93)90378-e
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic variables characterizing the induction of ventricular tachycardia versus ventricular fibrillation after myocardial infarction: Relation between ventricular late potentials and coupling intervals for the induction of sustained ventricular tachyarrhythmias

Abstract: Induction of ventricular fibrillation requires shorter coupling intervals than does induction of ventricular tachycardia. The presence of ventricular conduction delay seems to be a marker of facilitated induction of sustained monomorphic ventricular tachycardia rather than of ventricular fibrillation. The coupling intervals required to induce ventricular tachycardia or fibrillation are longer in patients with than in those without an abnormal signal-averaged ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…These investigators demonstrated that induction of monomorphic VT was a reproducible and specific response to PES, whereas the initiation of ventricular fibrillation (VF) and polymorphic VT was nonspecific. These conclusions were supported by subsequent studies 12–21 . All of these studies suggested that the optimal method to achieve maximum sensitivity and specificity for VT induction using PES was a protocol incorporating three extrastimuli from the RV apex and RV outflow tract (RVOT), during at least two drive cycle lengths (600 and 400 msec).…”
Section: Mechanismsmentioning
confidence: 80%
See 1 more Smart Citation
“…These investigators demonstrated that induction of monomorphic VT was a reproducible and specific response to PES, whereas the initiation of ventricular fibrillation (VF) and polymorphic VT was nonspecific. These conclusions were supported by subsequent studies 12–21 . All of these studies suggested that the optimal method to achieve maximum sensitivity and specificity for VT induction using PES was a protocol incorporating three extrastimuli from the RV apex and RV outflow tract (RVOT), during at least two drive cycle lengths (600 and 400 msec).…”
Section: Mechanismsmentioning
confidence: 80%
“…These conclusions were supported by subsequent studies. [12][13][14][15][16][17][18][19][20][21] All of these studies suggested that the optimal method to achieve maximum sensitivity and specificity for VT induction using PES was a protocol incorporating three extrastimuli from the RV apex and RV outflow tract (RVOT), during at least two drive cycle lengths (600 and 400 msec).…”
Section: Mode Of Initiationmentioning
confidence: 99%
“…SAECG abnormalities are less common in patients with a history of VF. Late potentials on the SAECG are noticeable in only 21 to 65 percent of patients with VF [33,34]. Conversely, some studies reported spectral abnormalities in these patients that may be similar to those seen in patients with VT [35].…”
Section: Discussionmentioning
confidence: 91%
“…A higher prevalence of late potentials has been found in association with inducible VT than with ventricular fibrillation (VF) in an experimental myocardial infarction model [28]. Martinez-Rubio et al [26] noted that the mean of the square root of the voltage during the last 40 ms of the QRS complex is lower in patients with inducible VT than in patients with inducible VF. These authors concluded that the presence of ventricular late potentials is a marker for the inducibility of sustained monomorphic VT rather than of the likelihood of VF.…”
Section: Stratification Of Patients At Riskmentioning
confidence: 99%